2022
DOI: 10.1080/22221751.2022.2086069
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus infects human osteoclasts and blocks differentiation and bone resorption

Abstract: Bone-related complications are commonly reported following arbovirus infection. These arboviruses are known to disturb bone-remodeling and induce inflammatory bone loss via increased activity of bone resorbing osteoclasts (OCs). We previously showed that Zika virus (ZIKV) could disturb the function of bone forming osteoblasts, but the susceptibility of OCs to ZIKV infection is not known. Here, we investigated the effect of ZIKV infection on osteoclastogenesis and report that infection of pre- and early OCs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…One of the top three affected pathways in fetal and offspring bone marrow cells was “osteoclast differentiation” ( Table S1-B and D ). Interestingly, it has been recently shown that ZIKV infection can affect osteoclast and osteoblast functions [ 28 , 29 ]. In addition to commonly affected proteins in fetuses and offspring, we also identified proteins uniquely affected in ZIKV offspring that were related to hematopoiesis (13 proteins) and bone marrow cancer (3 proteins) ( Figure 4 ; references are in File S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the top three affected pathways in fetal and offspring bone marrow cells was “osteoclast differentiation” ( Table S1-B and D ). Interestingly, it has been recently shown that ZIKV infection can affect osteoclast and osteoblast functions [ 28 , 29 ]. In addition to commonly affected proteins in fetuses and offspring, we also identified proteins uniquely affected in ZIKV offspring that were related to hematopoiesis (13 proteins) and bone marrow cancer (3 proteins) ( Figure 4 ; references are in File S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…45 Kellie A. Jurado et al 46 show that an increased number of Foxp3+ regulatory T cells were found in ZIKV-infected compared to mock-infected IFNAR1 −/− mice, further illustrating the importance of adaptive immunity in the ZIKV response. A recent study by Noreen Mumtaz et al 47 show that ZIKV infection disrupts osteoclast differentiation and function, and speculated that ZIKV-associated microcephaly may be involved. Claudia P. Figueiredo et al 36 report that ZIKV replication and TNF-α upregulation in adult brain tissue may induce synaptic and memory dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of HIV infection, bone resorption is promoted, with the extent influenced by the infection load 15,16 . On the other hand, Zika virus infection impedes bone remodeling in OC 17 . Research utilizing animal models suggests that SARS‐CoV‐2 affects bone metabolism both during acute infection and in the postrecovery phases 18–20 …”
Section: Introductionmentioning
confidence: 99%
“…15,16 On the other hand, Zika virus infection impedes bone remodeling in OC. 17 Research utilizing animal models suggests that SARS-CoV-2 affects bone metabolism both during acute infection and in the postrecovery phases. [18][19][20] This study examines the direct effects of SARS-CoV-2 on osteoclastogenesis, maturation, and resorption activity using osteoclast precursors from human peripheral blood mononuclear cells (PBMCs).…”
mentioning
confidence: 99%